Non-invasive Mechanical Ventilation in Lung Cancer: Physiological Principles and Clinical Utilization in Surgical and Non-surgical Settings - Marco Cascella; Antonio M. Esquinas (Thoracic Research and Practice)
Non-invasive mechanical ventilation (NIMV) has emerged as a pivotal intervention for the care of individuals with lung cancer. NIMV offers substantial advantages in enhancing oxygenation, optimizing respiratory function, elevating pulmonary capacities, and facilitating patient comfort. NIMV’s utility extends to enhancing clinical conditions that range from chronic obstructive pulmonary disease and emphysematous lung ailments to aiding patients with lung cancer facing acute respiratory failure. Furthermore, NIVM includes perioperative pulmonary rehabilitation. This approach is particularly relevant for individuals with limited lung capacity. Since both non-invasive positive pressure ventilation modes, including BiLevel positive airway pressure and continuous positive airway pressure, address the underlying pathophysiological mechanisms that contribute to postoperative respiratory failure, the proactive and early integration of NIMV has the potential to significantly enhance gas exchange and overall respiratory performance in meticulously chosen patients within the perioperative phase. Although non-intubated video-assisted thoracic surgery represents an interesting field of application for NIMV strategies, further studies are needed to optimize operative modalities. Lastly, NIMV has a pivotal role in the settings of intensive care and palliative care units, thereby cementing its versatile utility across various medical contexts.